2021
DOI: 10.1007/s00167-021-06485-z
|View full text |Cite
|
Sign up to set email alerts
|

Satisfactory patient-reported outcomes at 5 years following primary repair with suture tape augmentation for proximal anterior cruciate ligament tears

Abstract: Purpose An enhanced understanding of anterior cruciate ligament (ACL) healing and advancements in arthroscopic instrumentation has resulted in a renewed interest in ACL repair. Augmentation of a ligament repair with suture tape reinforces the ligament and acts as a secondary stabilizer. This study assesses the 5-year patient-reported outcomes of primary repair with suture tape augmentation for proximal ACL tears. Methods Thirty-seven consecutive patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…11,14,31,38,48,50 Recently, patient selection criteria for contemporary ACLSR have been proposed, and younger age (which may be a proxy for activities that are strenuous on the knee), (pursuit of) higher activity level, midsubstance ACL rupture location, lack of integrity of the ruptured ACL tissue and synovial sheath, and prolonged time from injury to surgery have been reported to negatively influence the outcomes of contemporary ACLSR techniques. 2,12,21,27,35,51,54 Except for timely operative treatment, none of the above factors were considered when including patients in the present study; included patients were young and athletically active, their inclusion was independent of ACL rupture location (although most patients had a proximal ACL rupture with <50% retraction of the synovial sheath), and the majority had a multilacerated tibial ACL remnant. 23 Thus, this might have negatively influenced the results for DA ACLSR in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,14,31,38,48,50 Recently, patient selection criteria for contemporary ACLSR have been proposed, and younger age (which may be a proxy for activities that are strenuous on the knee), (pursuit of) higher activity level, midsubstance ACL rupture location, lack of integrity of the ruptured ACL tissue and synovial sheath, and prolonged time from injury to surgery have been reported to negatively influence the outcomes of contemporary ACLSR techniques. 2,12,21,27,35,51,54 Except for timely operative treatment, none of the above factors were considered when including patients in the present study; included patients were young and athletically active, their inclusion was independent of ACL rupture location (although most patients had a proximal ACL rupture with <50% retraction of the synovial sheath), and the majority had a multilacerated tibial ACL remnant. 23 Thus, this might have negatively influenced the results for DA ACLSR in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective case series on nonaugmented and static augmented ACLSR have reported outcomes comparable with those reported in the present study. 7,22,27 Furthermore, in a prospective pilot study of 10 patients after DA ACLSR, Eggli et al 9 reported a median IKDCs of 98.9 with a range of 79.3 to 100 at the 5–year follow–up. In a prospective case series of 57 patients after DA ACLSR, Ahmad et al 1 reported a median IKDCs of 94.0 with a range of 63.2 to 100.0 at the 6–year mean follow–up.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Moreover, cases of re-rupture and other postoperative complications were still apparent. 17 , 18 , 19 Based on that account, more studies should be performed, not just only on ACL repair, but also ACL reconstruction and the benefits of internal suture tape for these techniques. After this case series, a randomized controlled study with a larger sample size should be performed, on patients undergoing ACL reconstruction with and without suture tape, with a long-term follow-up period, in order to precisely identify the overall benefits of suture augmentation to patients' subjective and objective outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Douoguih et al revealed a 14.8% re-rupture rate in their study of 27 patients with minimum 2-year follow-up and a similar study showed a rate of 6.9% in 29 patients [ 1 , 3 ]. Recently, a five-year follow-up prospective evaluation revealed a 17.6% re-rupture rate and they found those patients to be younger and have significantly higher activity levels than the rest of the cohort [ 9 ]. They also published a further study which revealed that those high-risk patients benefit from an additional ALL procedure, however, this was at short-term follow-up [ 8 ].…”
Section: Discussionmentioning
confidence: 99%